EGMR 39246/15 vom 27. Oktober 2020 , CASE OF REIST v. SWITZERLAND - [German Translation] summary by the Austrian Institute for Human Rights (ÖIM) - Hudoc Ch (2020)
No violation of Article 5 - Right to liberty and security (Article 5-1 - Procedure prescribed by law;Article 5-1-a - Competent court); No violation: 5;5-1;5-1-a